Perilaku Pencarian Informasi oleh pemustaka di Layanan Sirkulasi Perpustakaan Universitas Sumatera Utara - Nurhayati Gultom; Khoirunnisaa Khoirunnisaa; Nursyahada Sinaga; Sopa Rosa Lubis; Franindya Purwaningtyas (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to determine information search behavior by users in the service circulation of the University of North Sumatra Library. The method used in this research is descriptive qualitative. The data collection technique used in this research is observation. This study took the subject of the library users as informants and the object of research was information seeking behavior in the circulation of the University of North Sumatra Library. most of the visitors to the library are for the purpose of seeking information, only a small portion is for reading, thus giving rise to several possibilities for library visitors, such as; Some visitors come to the library for the purpose of information, reading and meditation. The information we get actually comes from a process of producing information. This is called information discovery theory, starting with: Initiation, formulation, exploration, formulation, collection, presentation. Human behavior in information sources and channels, including active and passive information seeking and use. Keywords: behavior, information search, library circulation